The Effect of Cutting Efficacy of Diamond Burs on Microleakage of Class V Resin Composite Restorations Using Total Etch and Self Etch Adhesive Systems - M.R. Malekipour; F. Shirani; S. Tahmourespour (Tehran University of Medical Sciences, 2010)
Objective: In this study, the effect of bur cutting efficacy was evaluated on microleakage of class V composite restorations with two adhesive systems. Materials and Methods: Class V cavities were produced on sound extracted human teeth, which had been assigned randomly to one of six groups (N=15) as follows: Groups 1 and 6 were prepared using used rough diamond bur; Group 2 and 5 were prepared using new rough diamond bur; Group 3 and 4 were prepared using soft diamond bur. After application of Single Bond (3M Dental Product, USA) in groups 4,5 and 6 and Clearfil SE Bond [ Kurary Medical Inc. Japan] in groups 1,2 and 3, all cavities were restored with composite resin. The teeth were thermocycled and microleakage was evaluated by dye penetration. Kruskal-Wallis and Mann-Whitney tests with Bonferroni's correction were used for statistical analysis. Results: The results showed that gingival margins significantly leaked more than occlusal margins for all bur types and bonding systems. Using the same adhesive system in gingival margins, significant difference was seen between bur types and using the same bur type in occlusal margins, there was a significant difference between the two types of adhesive systems. Conclusion: Cutting efficiency of bur had a great effect on microleakage of resin composite restorations. So long term use of burs may result in an increase in microleakage of composite resin restorations.